iCities Report: Localising the SDGs: Towards transformative actions and base planning in Albany (WA). - Llop i Torne, J. M.; Tardin-Coelho, Raquel; Perez Lopez, I (University of Newcastle Australia, 2025)
iCities Workshop: Localising the SDGs towards transformative actions is co-lead by the UNESCO Chair for Intermediate Cities, City of Albany and the University of Newcastle.The aim is collaboratively to build a local and global network to tackle common intermediate cities' challenges, propose solutions, disseminate good practices, and inform local government professionals concerning the SDGs with a particular focus on SDG 11 – Sustainable cities and communities: Make cities inclusive, safe, resilient and sustainable, and SDG 13 – Climate action: Take urgent action to combat climate change and its impacts. The methodology is based on the "Base Plan" methodology, an inclusive planning tool developed by UNESCO UdL-CIMES Chair for Intermediary Cities to identify "territorial logics" and strategic urban interventions. The Base Plan focuses on recognising, valuing and recovering the role of i-cities in the global network of urban-rural settings while accelerating transformative actions and projects aligned with the SDGs and the New Urban Agenda. The workshop assembles local governments employees, stakeholders, community members, and academics in the thinking-planning-proposing process as a collective endeavour to; 1) Verify how existing/future local plans (Strategic and Structure Plans) and projects meet the i-City's future development needs with attention to its intermediate relationships with its region (spatially and functionally), and; 2) Cross-check how existing/future local plans (Strategic and Structure Plans) and projects meet the SDGs (or not) and propose future ones for existing urban realities: urban, peri-urban, rural, natural, observing the following systems: Built environment; Infrastructure and flows; Natural environment; Productive Activities; Culture & Society.